CrkL meditates CCL20/CCR6-induced EMT in gastric cancer. Issue 2 (December 2015) - Han, Gang; Wu, Dawei; Yang, Yongan; Li, Zhiyun; Zhang, Jiapin; Li, Chengjun
Highlights CCR6 and CrkL expressed in gastric cancer tissues and cell lines. CCR6 and CrkL expression predicted poor prognosis of gastric cancer. Knockdown of CrkL abrogated CCL20-induced Erk1/2 signaling and EMT. Knockdown of CrkL affected CCL20-induced MGC803 migration and invasion.